2014
DOI: 10.1159/000360131
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Cardiac Computed Tomography Angiography in Patients with Suspected Coronary Artery Disease: A Meta-Analysis

Abstract: Objectives: The diagnostic accuracy of cardiac computed tomography angiography (CCTA) is well reported. The prognostic value of CCTA has been described in several studies, but many of these were underpowered and an update of the meta-analysis is necessary to increase the power to predict rare events.The purpose of this study was to perform a meta-analysis of the ability of CCTA to predict future cardiovascular events. Methods: We searched multiple databases for longitudinal studies of CCTA with a follow-up of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…We know lipid-lowering therapy is effective, but to date we have not considered the fact that when atherosclerosis is not present, it is extremely unlikely that major adverse cardiovascular events will develop. CCT and the prognostic data collected in the meta-analysis of Jiang et al [10] show a very low number of events in the group without CAD. This means that there may have been a pharmacological overtreatment in this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know lipid-lowering therapy is effective, but to date we have not considered the fact that when atherosclerosis is not present, it is extremely unlikely that major adverse cardiovascular events will develop. CCT and the prognostic data collected in the meta-analysis of Jiang et al [10] show a very low number of events in the group without CAD. This means that there may have been a pharmacological overtreatment in this group.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Cardiology we can read about the very precise and perceptive study carried out by Jiang et al [10 ]which provides a meta-analysis of prognostic studies performed with CCT. The authors assembled 18 studies that included 29,243 patients with a median follow-up of 25 months.…”
Section: Cardiac Computed Tomography: the Prognosticatormentioning
confidence: 99%
“…64 Moreover, overwhelming evidence supports the excellent mid-term and long-term prognosis after a negative cardiac CT examination, with an average annualized rate of major cardiac events as low as 0.21%. 65,66 This emphasizes a clinical value of cardiac CT for identification of patients with absence of coronary atherosclerotic plaques in whom no further additional testing and/or therapy is necessary or indicated.…”
Section: Cardiac Ctmentioning
confidence: 99%
“…We read with great interest the article ‘Prognostic value of cardiac computed tomography angiography in patients with suspected coronary artery disease: a meta-analysis' by Jiang et al [1], which was recently published in Cardiology . Based on a complex meta-analysis of 18 published studies, the authors found that coronary computed tomographic angiography (CCTA) could serve as a prognostic tool, being able to stratify the risk of adverse cardiovascular events based on the severity of coronary artery stenosis.…”
mentioning
confidence: 99%
“…Based on a complex meta-analysis of 18 published studies, the authors found that coronary computed tomographic angiography (CCTA) could serve as a prognostic tool, being able to stratify the risk of adverse cardiovascular events based on the severity of coronary artery stenosis. The study indicates an excellent prognosis for those with negative CCTA, while for the population with suspected coronary artery disease (CAD) and abnormal CCTA findings the authors found an incrementally increasing rate of major adverse cardiovascular events (MACE) with the increasing severity of coronary artery stenosis [1]. The study is well designed and leads to important conclusions.…”
mentioning
confidence: 99%